(1+[tex] 2^{2} [/tex] +[tex] 3^{3} [/tex]) : [tex] 2^{5} [/tex]=
(1+4+27) : 32=
=(5+27) : 32 =
=32 : 32 =
=1
[tex] 9^{0} [/tex] + [tex] 1^{8} [/tex] + [tex] 8^{1} [/tex] - [tex] 0^{1} [/tex] + [tex]0^{1996} [/tex] =
=1 + 1 + 8 - 0 + 0 =
= 2 + 8 - 0 + 0 =
=10 - 0 + 0 =
=10 + 0 =
= 0
[tex] 10^{1} [/tex] × [tex] 1^{10} [/tex] - [tex] 0^{9} [/tex] × [tex] 9^{0} [/tex] - [tex] 3^{5} [/tex] × [tex] 0^{1} [/tex] =
= 10 × 1 - 0 × 1 - 243 × 0 =
= 10 - 0 - 0 =
= 10 - 0 =
= 0
(7 + [tex] 11^{198} [/tex] : [tex] 11^{196} [/tex]) : 64 =
= (7 + [tex] 11^{198-196} [/tex]) : 64 =
= (7 + [tex] 11^{2} [/tex]) : 64 =
= (7+121) : 64 =
= 128 : 64 =
= 2